PENGARUH KOMPETENSI, INDEPENDENSI, ETIKA, PENGALAMAN AUDITOR, SKEPTISME PROFESIONAL AUDITOR, OBJEKTIFITAS DAN INTEGRITAS TERHADAP KUALITAS AUDIT (Studi Pada Kantor Akuntan Publik Di Kota Semarang) - Irwanti Bunga Nurjanah; Andi Kartika (Faculty of Economic and Business Universitas STIKUBANK, 2016)
This study examines the factors that affect the quality of audits at the existing KAP offices in the city of Semarang. This research was conducted in seven offices of KAP located in Semarang city by using auditor's analysis unit working in KAP office.The sampling method using Convenience sampling. The relationship or influence between variables is explained by using multiple linier regression analysis method and hypothesis test (t test). The results showed that the competence variables have a positive and significant impact on audit quality. The independence variable has a positive and significant influence on audit quality. The ethical variable of the auditor has a positive and significant influence on audit quality. The auditor experience variable has a positive and significant influence on audit quality. Professional skepticism audit variables have a positive and significant impact on audit quality,. The auditor's objectivity variable has a positive and significant influence on audit quality,. The auditor's integrity variable has a positive and significant influence on audit quality. Keywords: competence, independence, auditor ethics, auditor experience, professional skepticism of auditors, auditor objectivity, auditor integrity and audit quality.